KEDUDUKAN HUKUM PENGADILAN NIAGA DALAM KERANGKA SISTEM KEKUASAAN KEHAKIMAN (Faculty of Law, University of Palembang, 2023)
In the judicial power system that applies in Indonesia based on the 1945 constitution, there are four judicial bodies whose existence is recognized, namely the general court, the religious court, the state administrative court, and the military court. In addition, the law on judicial power also recognizes the existence of a special court as a specialty to adjudicate certain cases, one of these special courts is the commercial court which is authorized to adjudicate cases of bankruptcy and suspension of payment. However, the existence of the commercial court has not been regulated in a separate law, even though the regulation of the commercial court in a separate law is very important, because in practice the commercial court is not only authorized to adjudicate bankruptcy cases but is also authorized to adjudicate cases in the field of intellectual property rights.